RELAÇÃO HOMEM/NATUREZA E O LAZER COMO UMA POSSIBILIDADE DE SENSIBILIZAÇÃO DA QUESTÃO AMBIENTAL - Cheng Hsin Nery Chao (Motrivivência, 2004)
The present article has the objective to show that the leisure, while surrounding propitious for the development of practical educative transforming, can be a possibility of sensibilization for the ambient question. Key-words: leisure, ambient, sensibilization